1973
DOI: 10.1021/jo00959a034
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of .alpha.,.beta.-unsaturated esters. II. Syntheses of 2,3-diaryl-5-oxocyclopentane-1-carboxylates by hydrodimerization of cinnamates

Abstract: 2,3-Diaryl-5-oxocyclopentane-l-carboxylates (4) were synthesized in yields of 7-60% by electrolytic hydrodimerization of trans cinnamate esters in anhydrous acetonitrile-tetraethylammonium bromide at constant, controlled cathode potential. For ethyl cinnamate as substrate the hydrodimer was found to have the froras-diphenyl geometry. A mechanism for the formation of 4, involving steps of (a) ß,ß coupling of oriented anion radicals at the electrode surface, (b) protonation of the dinegative anion by an availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…Recently, Fussing et al [23] reported that cathodic reduction of cinnamic acid esters in DMF results initially in coupling of two radical-anions at C-3 followed by a Dieckmann condensation to afford the corresponding cyclic hydrodimers. In the present investigation, we observed that electrolysis of 4 in DMF containing 0.10 M TEABF 4 at a reticulated vitreous carbon cathode conducted at a potential maintained at approximately )1.25 V gave the same cyclic hydrodimer reported by Klemm and Olson [16], but we did not carry out any quantitation of the product. In the presence of a proton donor (phenol), macroscale reductions of cinnamic acid esters conducted at a cathode potential somewhat more negative than the second (or coalesced wave) leads to saturation of the carbon-carbon double bond and most likely involves protonation at C-2 as the rate-determining step [32,33].…”
Section: Controlled-potential Electrolysis Of Ethyl 2-bromo-3-(3 0 ; supporting
confidence: 55%
See 1 more Smart Citation
“…Recently, Fussing et al [23] reported that cathodic reduction of cinnamic acid esters in DMF results initially in coupling of two radical-anions at C-3 followed by a Dieckmann condensation to afford the corresponding cyclic hydrodimers. In the present investigation, we observed that electrolysis of 4 in DMF containing 0.10 M TEABF 4 at a reticulated vitreous carbon cathode conducted at a potential maintained at approximately )1.25 V gave the same cyclic hydrodimer reported by Klemm and Olson [16], but we did not carry out any quantitation of the product. In the presence of a proton donor (phenol), macroscale reductions of cinnamic acid esters conducted at a cathode potential somewhat more negative than the second (or coalesced wave) leads to saturation of the carbon-carbon double bond and most likely involves protonation at C-2 as the rate-determining step [32,33].…”
Section: Controlled-potential Electrolysis Of Ethyl 2-bromo-3-(3 0 ; supporting
confidence: 55%
“…1 (curve B), 4 is reduced in stepwise fashion at more negative potentials. It is well documented [16,31] that cinnamic acid esters undergo highly stereoselective electrohydrodimerization. Klemm and Olson [16] demonstrated that reduction of 4 in acetonitrile containing 0.05 M tetraethylammonium bromide gives a cyclic hydrodimer (2,3-bis-(3 0 ; 4 0 -dimethoxyphenyl)-5-oxocyclopentanecarboxylic acid ethyl ester).…”
Section: Controlled-potential Electrolysis Of Ethyl 2-bromo-3-(3 0 ; mentioning
confidence: 99%
“…the kinetic stability, of the radical anions is decisively enhanced by the presence of a sulfur centre in -0.71 0.40 a versus the internal Ag/Ag + /AgBr/Brreference electrode; b according to ref. [4], measured at a sweep rate of 500 mVs -1 . the coumarin system although the one-electron reduction of thionocoumarins is achieved at less negative reduction potentials (Table 1), which should be indicative of a higher thermodynamic stability of the radical anions compared with the corresponding carbonyl derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…3 As a result, unsubstituted cinnamic as well as acrylic derivatives easily undergo hydrodimerisation at the β-position. 4 The same is obviously true for coumarins and thiocoumarins without a substituent in the 4-position, the radical anions of which are unstable according to a preliminary study. We chose, therefore, the sterically protected 4-methylcoumarin derivatives for our investigation.…”
mentioning
confidence: 85%
“…The GC electrode provided the coupling product 2 (34%, racemate/meso = 74:26) and E - 3 (25%), along with 41% of 1a . Similar cathodic reductions of cinnamate derivatives were carried out using Hg [ 10 11 ], Cu [ 12 13 ], Pb [ 13 14 ], Zn [ 13 ], Sn [ 13 ], and Ag [ 13 ], and the major products were the cyclic products (type 3 ) through Diekmann-type cyclization, whereas the hydrodimer 2 was the predominantly produced product in the present BDD electrode mediated reduction. Despite a different product ratio, the GC electrode gave similar reaction products to that of the BDD electrode.…”
Section: Resultsmentioning
confidence: 53%